Putting social science to work : the ground between theory and use explored through case studies in organisations - Klein, Lisl; Eason, Ken (Cambridge University Press, 1991)
In this book, first published in 1991, Lisl Klein and Ken Eason look at the various issues involved when attempts are made to make use of the theories, methods and findings of the social sciences in practical affairs. They consider how human and social considerations may be successfully integrated with technical and economic ones in the design and development of organisations and work. Their study is both empirical and theoretical. Its core is the examination of fourteen case studies from manufacturing and service organisations in Britain and Germany. The book concludes with a discussion of what contributes to a successful practice. Its findings will be invaluable to all social scientists interested in the application of their disciplines as well as to potential clients in the world of business and industry